Aspergillus terreus (Trichocomaceae): A Natural, Eco-Friendly Mycoinsecticide for Control of Malaria, Filariasis, Dengue Vectors and Its Toxicity Assessment Against an Aquatic Model Organism Artemia nauplii - Ragavendran, C.; Srinivasan, R.; Kim, Myunghee; Natarajan, Devarajan (Frontiers in Pharmacology, 2018)
The present study was aimed to evaluate the neurobehavioral toxicity, knock-down effect, histopathology, ovicidal, adulticidal and smoke toxicity effect of Aspergillus terreus extract against three mosquito species, namely Anopheles stephensi, Culex quinquefasciatus and Aedes aegypti (Diptera: Culicidae). The isolated fungal strain was identified as A. terreus (GenBank Accession No: KX694148.1) through morphological and molecular (phylogenetic) analysis. The morphological changes in the treated fourth instar larvae shown the demelanization of cuticle and shrinkage of the internal cuticle of anal papillae. The time duration of extract exposure against the larvae determines the level of toxicity. . The results of the biochemical analysis indicated that a decrease in the level of acetylcholinesterase, α-carboxylesterase, and β-carboxylesterase in extract treated fourth instar larvae of all tested mosquito species. The findings of histopathological investigation shown the disorganization of the abdominal region, mainly in mid, hindgut and gastric caeca, loss of antenna, lateral hair, caudal hair, upper and lower head hairs in the mycelium extract treated An. stephensi, Cx. quinquefasciatus and Ae. aegypti. The ovicidal bioassay test results showed the mosquito hatchability percentage was directly related to the concentrations of mycelium extract. Nil hatchability of mosquito eggs was noticed at 500 µg/ml concentration. The adulticidal activity of fungal mycelia ethyl acetate extract resulted in a dose-dependent activity (15 and 30 min recovery periods). The better adulticidal activity was observed in the ethyl acetate extract against An. stephensi, Cx. quinquefasciatus followed by Ae. aegypti with the best score of LD50 and LD90 values and nil mortality was found in the control. The results of smoke toxicity assay of the mycelia extract exhibited significant mortality rate against Ae. aegypti (91%), Cx. quinquefasciatus (89%) and An. stephensi (84%). In addition, the present investigation reported the stability and toxic effects of A. terreus mycelium ethyl acetate extract on Artemia nauplii. . The outcome of the present study, suggest that the A. terreus metabolites might serve as an alternative, cost-effective, eco-friendly and target specific mosquitocidal agent in the future.